2021
DOI: 10.1088/2053-1591/ac1c35
|View full text |Cite
|
Sign up to set email alerts
|

Progress on microstructure features and creep properties of prospective Tin-Silver-Zinc alloy using a magnetic field

Abstract: In the current work, applying a rotating magnetic field (RMF) is an innovative approach to improve the microstructure features and creep resistance of Sn-2.0Ag-2.0Zn (SAZ) alloy. The results revealed that RMF does not change intermetallic compounds (IMCs) constituents furthermore SAZ alloy with applying a magnetic field (SAZ-B) exhibited microstructure refinement and homogeneous distribution of IMCs. Moreover, SAZ-B displayed more creep resistance (∼366%) and greater creep rupture time (∼56.4%) than those of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…Wei et al [ 49 ] reported the same three phases for the Sn–3.7 wt% Ag–0.9 wt% Zn alloy. In a study with the ternary Sn–2 wt% Ag–2 wt% Zn alloy, Hammad et al [ 50 ] observed similar XRD patterns as compared to those presented here, identifying the β‐Sn, Ag 3 Sn, ζ‐AgZn, and Ag 5 Zn 8 phases.…”
Section: Resultssupporting
confidence: 81%
“…Wei et al [ 49 ] reported the same three phases for the Sn–3.7 wt% Ag–0.9 wt% Zn alloy. In a study with the ternary Sn–2 wt% Ag–2 wt% Zn alloy, Hammad et al [ 50 ] observed similar XRD patterns as compared to those presented here, identifying the β‐Sn, Ag 3 Sn, ζ‐AgZn, and Ag 5 Zn 8 phases.…”
Section: Resultssupporting
confidence: 81%
“…In detail, the experiment and apparatus were explained in references. 16,42 Alloy compositions were analyzed by the x-ray fluorescence (XRF) analytical technique, as shown in Table 1. SAC205 and SAC205-B samples were annealed for 30 min at 130 °C before being naturally air-cooled to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13] Furthermore, thermal and creep features are known as the most controlling deformations to expect the reliability, lifetime, and microstructure analysis of advanced interconnection solder alloys. [14][15][16][17] Moreover, creep occurrence is considered a great challenge in industrial applications. Thus, understanding the creep properties of a material can help predict its lifetime and recognize the breakdown behaviors of microelectronic packages.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Yin et al [40] and Sun et al [41] demonstrated that inductive heating of the binary system Cu-Sn leads to significantly faster intermetallic phase formation of Cu 6 Sn 5 and Cu 3 Sn. Moreover, Hammad et al was able to achieve significantly improved microstructure features and mechanical properties of inductively heated tin-silver-zinc alloys after IMC formation [42]. Furthermore, induction heating can be used for sintering of micro-scaled silver particles to bond microelectronic components at chip-level [43].…”
Section: Introductionmentioning
confidence: 99%